Further Developments Relating to the Certification of Explosives for Sale in European Union Countries - R. K. Wharton; G. H. Pickering (International Society of Explosives Engineers, 2004)
The paper reviews the explosives products that have been certified by the different Explosives Notified Bodies for sale in European Union countries. The development of harmonised standards for explosives is also discussed as are recent developments relating to certification and a possible forthcoming Directive on pyrotechnic articles.Copyright